Immune cells: the key mediator between the gut microbiota and osteoporosis - Ma, Tianyi; Zhang, Tiantian; Peng, Chengqi; Liu, Ke; Xiong, Yixiao; Chen, Keru; Peng, Nazi; Wei, Zhentao; Kuang, Jianjun; Ou, Liang (Frontiers in Immunology, 2025)
As the body’s largest immunological interface, the intestine harbors a complex ecosystem of gut microbiota (GM) that orchestrates mucosal immune maturation while sustaining local immunological equilibrium. Emerging evidence reveals the gut’s influence on skeletal homeostasis via neuro-immune-endocrine pathways—termed the gut-bone axis—though its mechanistic intricacies remain incompletely defined. Since the concept of osteoimmunology was proposed in 2000 by Arron & Choi, immune-skeletal interactions have garnered significant research traction. Immune cells primarily contribute to the maintenance of bone homeostasis through the release of pro- and anti-inflammatory factors. Consequently, the immune system represents a crucial intermediary in understanding the relationship between GM and metabolic bone diseases. This review synthesizes the interrelationships among gut microbiota, immune cells, and osteoporosis, and elucidates how GM modulate bone metabolism in osteoporosis through this critical intermediary. Furthermore, building upon the microbiome–immune–bone axis, we highlight several emerging microbiota-targeted interventions—such as probiotics, prebiotics, dietary modifications, fecal microbiota transplantation, and engineered microbes—and evaluate their clinical translational potential, with the aim of advancing diagnostic and therapeutic strategies for metabolic bone disorders.